2016
DOI: 10.1089/scd.2016.0035
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Immortalization Enables Seamless Transdifferentiation of Primary Fibroblasts into Other Lineage Cells

Abstract: Fibroblasts can be transdifferentiated directly into other somatic cells such as cardiomyocytes, hematopoietic cells, and neurons. An advantage of somatic cell differentiation without first generating induced pluripotent stem cells (iPSCs) is that it avoids contamination of the differentiated cells with residual iPSCs, which may cause teratoma. However, since primary fibroblasts from biopsy undergo senescence during repeated culture, it may be difficult to grow transdifferentiated cells in sufficient numbers f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The immortalization of cells with hTERT has many potential advantages over other immortalization methods. Fibroblasts immortalized with SV40 large T antigen may accumulate chromosomal rearrangements, whereas fibroblasts immortalized with hTERT retain the control karyotype [ 31 ], which enables studies with less artificially changed cells.…”
Section: Discussionmentioning
confidence: 99%
“…The immortalization of cells with hTERT has many potential advantages over other immortalization methods. Fibroblasts immortalized with SV40 large T antigen may accumulate chromosomal rearrangements, whereas fibroblasts immortalized with hTERT retain the control karyotype [ 31 ], which enables studies with less artificially changed cells.…”
Section: Discussionmentioning
confidence: 99%
“…Immortalizing genes-SV40T [40], hTERT [42], or their combination (SV40T + hTERT [38,39,106])-are flanked by two homodromous LoxP sites [107,108] or two flippase recognition target (FRT) sites [109][110][111][112][113] and are delivered by a retroviral vector [107,108,110,111,114,115], CRISPR/Cas9 system [54], or by the PiggyBac transposon system (transposonmediated vector pMPH86) [55,112,113], which is one of the two most widely used transposon systems (PiggyBac, Sleeping Beauty) [56,116,117] and exhibits higher transposition activity than Sleeping Beauty in cultured human cells [117].…”
Section: Site-specific Recombinationmentioning
confidence: 99%
“…Mitotic errors can lead to the appearance of tumorigenic genotypes [146]. Indeed, it has been shown that cells immortalized with hTERT + SV40T, SV40Tor HPV16 E6/E7-immortolized cells (as opposed to cells immortalized with hTERT alone) demonstrated abnormal karyotypes, including complex chromosome loss [106], hypodiploid or aneuploid karyotypes [139], and features such as the absence of contact inhibition [106].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to solve the lifespan problem with primary cells such as fibroblasts, reversible immortalization could be performed to increase the number of passages and limit the risk for the development of aberrations in the genome[128]. In one study, this reversible immortalization was performed in primary neonatal rat cardio-myocytes using lentiviral transduction with either simian virus 40 large T antigen (TAg) or Bmi-1 together with the human telomerase reverse transcriptase (hTERT).…”
Section: Fibroblasts Vs Ipscsmentioning
confidence: 99%